Full and Modified Glasgow-Blatchford Bleeding Score in Predicting the Outcome of Patients with Acute Upper Gastrointestinal Bleeding; a Diagnostic Accuracy Study - Shahrami, Ali; Ahmadi, Saba; Safari, Saeed (Archives of Academic Emergency Medicine, 2018)
Introduction: Screening of high risk patients and accelerating their treatment measures can reduce the burden of the disease caused by acute upper gastrointestinal (GI) bleeding. This study aimed to compare the full and modified Glasgow-Blatchford Bleeding Score (GBS and mGBS) in prediction of in-hospital outcomes of upper GI bleeding. Methods: In the present retrospective cross-sectional study, the accuracy of GBS and mGBS models were compared in predicting the outcome of patients over 18 years of age with acute upper GI bleeding confirmed via endoscopy, presenting to the emergency departments of 3 teaching hospitals during 4 years. Results: 330 cases with the mean age of 59.07 ± 19.00 years entered the study (63.60% male). Area under the curve of GBS and mGBS scoring systems were 0.691 and 0.703, respectively, in prediction of re-bleeding (p = 0.219), 0.562 and 0.563 regarding need for surgery (p = 0.978), 0.549 and 0.542 for endoscopic intervention (p = 0.505), and 0.767 and 0.770 regarding blood transfusion (p = 0.753). Area under the ROC curve of GBS scoring system regarding need for hospitalization in intensive care unit (0.589 vs. 0.563; p = 0.035) and mortality (0.597 vs. 0.564; p = 0.011) was better but the superiority was not clinically significant. Conclusion: GBS and mGBS scoring systems have similar accuracy in prediction of the probability of re-bleeding, need for blood transfusion, surgery and endoscopic intervention, hospitalization in intensive care unit, and mortality of patients with acute upper GI bleeding.